“I [Won’t] Follow You”: The Misguided, and Dangerous, Interpretation of Constitutional Extraterritoriality in United States v. Ali - Isaac D. Chaput (Washington University Law Review, 2014)
Not only is United States citizenship a “high privilege,” it is a priceless treasure. For that citizenship is enriched beyond price by our goal of equal justice under law—equal justice not for citizens alone, but for all persons coming within the ambit of our power.
Keywords: United States v. Ali; citizenship; extraterritoriality; equal justice